Simple Resistance Exercise for 24 Weeks Decreases Alanine Aminotransferase Levels in Patients with Non-Alcoholic Fatty Liver Disease - Takahashi, Atsushi; Imaizumi, Hiromichi; Hayashi, Manabu; Okai, Ken; Abe, Kazumichi; Usami, Keiji; Tanji, Nobuo; Ohira, Hiromasa (Sports Medicine International Open, 2017)
Exercise therapy is effective and recommended for non-alcoholic fatty liver disease (NAFLD) based on the efficacy of hepatic fat reduction. However, the efficacies of exercise therapy are based on short-term intervention. Moreover, no reports have examined whether significant reductions in serum levels of alanine aminotransferase (ALT) are achieved with exercise therapy in patients with NAFLD. The aim of this study is to assess the effects of simple resistance exercise for 24 weeks in NAFLD. 59 patients with NAFLD were assigned to a resistance exercise group (n=28) or a control group (n=31). The resistance exercise group performed 2 exercises (push-ups and squats) 3 times a week on nonconsecutive days for a trial periods of 24 weeks. Patients in the control group proceeded with regular physical activities under a restricted diet throughout the study. The effects of exercise were compared between groups after 24 weeks.Mean ALT level, homeostasis model assessment-estimated insulin resistance index and hepatic steatosis grade were all decreased in the resistance exercise group. Changes in ALT levels correlated negatively with changes in muscle:body weight ratio in the exercise group.These data demonstrate that 24 weeks of simple resistance exercise comprising squats and push-ups represents an effective treatment for NAFLD.
Keywords: NAFLD; resistance exercise; ALT; 24 weeks